The Role Of Al-Munasabah In The Interpretation Of The Qur'an (A Study of the Book of Nadzmu Duror by al-Biqō'i) - Mohamad Muhtarom Ali; Muhamad Afifudin Dimyathi; Ach. Khoiri Nabil; Ahnaf Gilang Ramadhan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study examines the role of the concept of al-munāsabah (the interrelation between verses and surahs) in the interpretation of the Qur'an based on Nadzmu Duror by Al-Biqā’i. This concept plays a crucial role in revealing the structure and deep meanings between the verses of the Qur'an. The primary objective of this research is to explore the application of al-munāsabah in Al-Biqā’i’s exegesis and identify its contribution to understanding the Qur'an’s meaning. This study employs a qualitative-descriptive method with a textual analysis approach, focusing on an in-depth literature review of Nadzmu Duror and other supporting sources.The findings indicate that Al-Biqā’i uses al-munāsabah as a central approach to connect verses and surahs, thereby strengthening the thematic context and meaning of the Qur'an. This study also reveals how Al-Biqā’i applies al-munāsabah to interpret verses in an integrative and contextual manner, providing new perspectives in Qur'anic exegesis. This concept helps uncover the beauty of the Qur'an’s structure and deepens the understanding of its embedded messages. These findings affirm that al-munāsabah makes a significant contribution to enriching exegetical approaches, particularly in understanding the internal structure of the Qur'an, and offer important implications for the development of structural-based Qur'anic studies.